Investigating the thermal transport in gold decorated graphene by opto-thermal Raman technique. (7th January 2022) - M K, Ranjuna; Balakrishnan, Jayakumar
Abstract: We report a systematic study on the thermal transport properties of gold nanoparticles (Au NPs) decorated single-layer graphene on a SiO2 /Si substrate by the opto-thermal Raman technique. Our results, with moderate Au NPs coverage (<10%), demonstrate an enhancement in the thermal conductivity of graphene by ∼55% from its pristine value and a decrement in the interface conductance by a factor of 1.5. A detailed analysis of our results shows the importance of the photo-thermal conversion efficiency of Au NPs, plasmon–phonon coupling and lattice modifications in the graphene developed after gold nanoparticles deposition in enhancing the thermal conductivity and reducing the interface thermal conductance of the system. Our study paves way for a better understanding of the thermal management in such hybrid systems, which are envisioned as excellent candidates for optoelectronics and photonics applications.